STUDY ABOUT THE IMPACT OF THE FREE THROW IN BASKETBALL GAMES ENDED AT THE DIFFERENCE NO GREATER THAN 2 POINTS DURING THE 2018-2019 ROMANIA’S MEN’S NATIONAL BASKETBALL LEAGUE SEASON (University Arena, 2024)
Background. Basketball is one of the most popular team sports in the world. It stands out through the finesse, accuracy, fantasy of the technical and tactical exercises, athletes’ height and physical qualities, all of these merged into a competition, which requires team spirit, sacrifice, intelligence and nervous resistance. It is a team sport which demands a large array of technical skills, tactical actions from the simplest to the most complex. This research aims to highlight the importance of free-throws in the economy of basketball games played in the men’s first division through the coefficient of the made free-throws by selecting all the games ended at a difference no greater than 2 points.Objectives. The objectives of this research are: influencing the development of morpho-functional body types, the development of movement quality, the development of a wide tactical knowledge, the introduction of new technical methods, increasing the overall performance. One of the main goals of this paper is to provide a detailed analysis of games ended at a difference of no more than two points.Methods. The methods used in the following research consist of video recording, match statistics and data analysis of official games played in the 2018-2019 Men’s National Basketball League season.Results. The results of this research show that the average made shot percentage of Men’s National Basketball League is 67,9 %. Returning to the problem of developing a tactical cognitive process regarding the importance of the free-throw, we need to mention that the foundation of this process is knowing the basics of the game, on which we can build and perfect the skills acquired along the years.Conclusion. The free-throw in the basketball game it’s taken in various muscular effort conditions. Thus, the players can benefit of a free-throw after greater or lesser effort. The content of the training, its effectiveness and variability are important to achieve for this purpose. The free-throw is a test of finesse, high coordination, accuracy, in which the information received from the brain an essential role. The basketball game requires an equal development of the entire complex of motor qualities through its wide motor content and the variety of movement it requires. This is why the players need a continuous and perseverant preparation.
Keywords: free – throw; two points; difference; made shot